Lower socioeconomic status is associated with recurrent shoulder instability before surgical shoulder stabilization - Mahdi N. Mazeh; Joshua P. Castle; Johnny Kasto; Brittaney Pratt; Eric X. Jiang; Matthew Gasparro; Lawrence Enweze; Jared M. Mahylis; Vasilios Moutzouros; Stephanie J. Muh (Journal of Orthopaedic Surgery and Research)
Abstract Background Social determinants of health (SDOH) encompass social and economic factors that influence healthcare access and outcomes. In orthopaedic surgery, disparities in SDOH contribute to unequal access to care and differences in post-surgical recovery. Prior studies indicate that an increased number of preoperative shoulder dislocations raises the likelihood of recurrent instability following stabilization procedures. However, limited research explores the association between SDOH and preoperative dislocation frequency. This study examines how SDOH factors influence the number of shoulder dislocations before surgical intervention. Methods Patients that underwent shoulder instability surgery at a single center in a large metropolitan area between January 1, 2021, and April 30, 2023, were identified. Patients’ demographic and social determinant variables were extracted using the electronic medical record. Socioeconomic status was assessed using the Social Vulnerability Index (SVI) and the Area Deprivation Index (ADI), based on patient zip codes. Statistical analyses, including univariate and multivariate regression models, evaluated predictors of multiple dislocations before surgery, focusing on factors such as age, body mass index (BMI), and socioeconomic indicators. Results Among 106 patients, 54% identified as White, 29% as Black, and 17% as other. Thirty-eight (35.8%) had a single dislocation before surgery, while 68 (64.2%) experienced multiple instability events. Univariate analysis showed younger age (odds ratio [OR] 0.94, P = 0.02), lower BMI (OR 0.90, P = 0.02), higher SVI (OR 1.21, P = 0.006), and higher ADI (OR 6.04, P = 0.003) were associated with recurrent instability. Multivariate analysis confirmed lower BMI (OR 1.15, P = 0.02) and higher ADI (OR 7.46, P = 0.02) as independent predictors. Conclusions Lower socioeconomic status, as measured by ADI, is an independent predictor of a higher likelihood of recurrent instability before surgery. Recognizing these relationships can motivate surgeons to create pathways to prevent these treatment disparities among shoulder instability patients. Level of evidence III retrospective cohort study.